Pengembangan Inovasi Dan Kreativitas Dalam Ekonomi Sirkular : Menuju Masa Depan Berkelanjutan - Sijabat , Ferdi Nazirun; Syarifah Mauli Masyithah; Fikrah Humaimah (Bansigom Na Publisher, 2024)
Advancements in science and technology, as well as increased national development activities, have opened up many opportunities for society in various aspects of life. In the era of globalization, Indonesia faces complex challenges such as limited capital, changing mindsets, lifestyles, and the increasingly dynamic needs of the community. Technology-based innovation is key to facing global competition and is a major factor in the economic growth of both developed and developing countries. To achieve a circular economy, innovation and creativity need to permeate various aspects, from production processes to distribution and consumption. The circular economy emphasizes the sustainable use of resources and waste reduction. This requires close collaboration between the government, industry, academia, and the public. The government plays a crucial role in supporting and facilitating the development of innovation and creativity through supportive policies, funding, and the provision of adequate infrastructure